Efficacy and Tolerability of Cranial Electrotherapy Stimulation in the Treatment of Anxiety: A Systemic Review and Meta-Analysis - Ching, Pao-Yuan; Hsu, Tien-Wei; Chen, Guan-Wei; Pan, Chih-Chuan; Chu, Che-Sheng; Chou, Po-Han (Frontiers in Psychiatry, 2022)
Objective: We aimed to investigate the efficacy and tolerability of cranial electrotherapy stimulation (CES) for patients with anxiety symptoms. Method: We searched the Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL), Embase and Medline for randomized control trials (RCTs) from the time of inception until November 15, 2021, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data were pooled using a random-effects model. The primary outcomes were the mean change scores for anxiety symptoms. The secondary outcomes were the mean change scores for depressive symptoms. Results: Eleven RCTs were eligible (n = 794, mean age: 41.4, mean population of female: 64.8%). CES significantly reduced the anxiety symptoms compared to the control group (k = 11, n = 692, Hedge’s g = -0.625, 95% confidence intervals [CIs] = -0.952 to -0.298, p < 0.001) with moderate effect size. The subgroup analysis showed that CES reduced both primary and secondary anxiety (primary anxiety, k =3, n = 288, Hedges’ g = -1.218, 95 % CIs = -1.418 to -0.968, p = 0.007; secondary anxiety, k = 8, n = 504, Hedges’ g = -0.334, 95 % CIs = -0.570 to -0.098, p = 0.006). After performing between group analysis, we found CES has significant better efficacy for patients with primary anxiety than those with secondary anxiety (p < 0.001). For secondary outcome, CES significantly reduced depressive symptoms in patients with anxiety disorders (k = 8, n = 552, Hedges’ g = -0.648, 95% CIs = -1.062 to -0.234, p = 0.002). No severe side effects were reported and the most commonly reported adverse events were ear discomfort and ear pain. Conclusion: We found CES is effective in reducing anxiety symptoms with moderate effect size in patients with both primary and secondary anxiety. Furthermore, CES was well tolerated and acceptable.